Timber Trade in the Eastern Democratic Republic of the Congo (DRC): Effectiveness of Timber Parks in Tackling Tax Frauds - Ferrari, S.; Cerutti, P.O. (Commonwealth Forestry Association, 2023)
HIGHLIGHTS The DRC Government has adopted and run an innovative ‘timber park' model to check timber trade and exports in the eastern part of the country. The ‘timber park' was able to detect various potentially egregious forms of illegalities, but also learn from observed illegalities, adapt its procedures, and improve its performance over time. In the case of transiting timber, which is sealed at origin and not checked at the park, it was possible to detect the very worrying trend that 100% of export declarations mention only one, and the same tree species. The park staff were able to detect the clear mismatch between what was declared as Mammea africana and belonged instead to the genus Afzelia, commercial name doussié, possibly A. bipindensis, one of the most valuable species (in terms of taxation) and also part of the country's most threatened species, recently listed in Annex II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Many species of the genus Entandrophragma spp (sipo, kosipo, sapelli, tiama) were observed by the park staff but never declared in transport waybills. More laboratory analyses are recommended to verify the exported species. SUMMARY The Democratic Republic of the Congo (DRC) shares borders with nine countries and has around 150 million hectares of tropical moist forests. A moratorium on logging titles has been in place since 2002 and infrastructure is very poor. The country plans to lift the moratorium and invest in infrastructure as part of the broader East-African road and railway networks. We present a case-study conducted for thirty months (2020-2022) on timber trade and export at the first ‘timber park' established on the eastern border. Multiple forms of potentially illegal timber trade were detected. In the case of transiting timber, results indicate that 100% of export declarations mention only one, and the same tree species. There also exist several mismatches between declared vs actually exported species (e.g. Mammea africana instead of genus Afzelia, recently listed in Annex II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES)). We estimate the potential financial losses for the DRC Government and discuss possible improvements. The model's extension to major border crossings could contribute to both sectoral improvements and better environmental policies. Yet results also indicate that the model's replication, sustainability and effectiveness can only occur and be maintained if interest and political support by provincial governments and their field staff remain strong.